DIRECT CAROTID CAVERNOSUS FISTULA: Poster Presentation - Case Report - Resident - Monica Camilla Chandra; Stevanus Paliliewu; Robby Tumewu; Gilbert Tangkudung (Majalah Oftalmologi Indonesia, 2023)
Abstract Introduction : Carotid cavernous fistula (CCF) is an abnormal communication between the cavernous sinus and the carotid arterial system, most commonly due to head trauma from a basal skull fracture creating a tear in the internal carotid artery (ICA) within the cavernous sinus. Case Illustration : A 15 years old girl presented with orbital pain, swelling, swishing or buzzing sounds, headache, and vision loss. Five months ago, she had a history of traumatic injury and undergone craniotomy. From physical examination Orbital ultrasound presence with dilated superior ophthalmic vein, which appears as a hollow tubular structure with no internal echo. MRI scan show a mass suggestive carotid cavernosus fistula dextra. DSA result confirmed the diagnose as direct carotid cavernosus fistula dextra as communication between internal carotid artery and sinus cavernosus. The patient was treated with neuroprotective along medication followed by endovascular treatment from the neurointervention department. Discussion : The classic triad of CCF includes pulsatile exophthalmos, chemosis and orbital bruit. Ophthalmic manifestations of CCFs vary widely depending on underlying aetiology, type, size, location, blood flow rate and drainage route of the CCF. Patient initially undergo noninvasive imaging with orbital ultrasound and magnetic resonance imaging (MRI). Digital subtraction angiography is the gold standard in the diagnosis of CCF and must be performed before any potential intervention. Conclusion : This case describes a patient who was diagnose with direct carotid cavernous fistula of the right eye.